A new donor-acceptor conjugated polymer-gold nanoparticles biocomposite materials for enzymatic determination of glucose. (1st December 2020) - Tan, Burcu; Baycan, Fatma
Abstract: In this study, the monomer 3-(5, 8-bis (2, 3-dihydrothieno[3, 4-b][1, 4]dioxin-5-yl) -3-(9- hexyl-9H-carbazole-3-yl)quinoxalin-2-yl) -9-hexyl9H-carbazole (HCQE) was electropolymerized on the graphite pencil electrode for the first time and used as a glucose biosensor. After electropolymerization, enrichment with Au nanoparticles was performed to amplify the signal (PHCQE/AuNPs). Following the electropolymerization step, glucose oxidase (GOx) immobilization was performed on the conjugated polymer coated graphite pencil electrode (GPE) surface using glutaraldehyde (GA) as crosslinking reagent due to strong π-π* conjugation on the polymer backbone (PHCQE/AuNPs/GOx). Voltammetric determination was also performed by monitoring the oxygen consumption against Ag/AgCl reference electrode at −0.7 V in phosphate buffer solution (0.10 mM; pH 7.4). The new PHCQE/AuNPs/GOx biosensor showed a linear response for glucose in the concentration range between 0.75 and 3.125 mM (LOD: 0.017 mM) along with a good sensitivity (0.13μA/mM −1 ). To examine the selectivity of the PHCQE/AuNPs/GOx biosensor, citric acid, fructose, sucrose, galactose, L-ascorbic acid, mannose, dopamine and salicylic acid were studied in the same buffer solution. The conjugated polymer PHCQE enriched with Au nano particles provides enzyme immobilization effectively. The applicability of the biosensor in the commercial samples has been also investigated and we have found that the conjugated polymer PHCQE enriched with Au nano particles is very effective for the determination of glucose in commercial samples. Graphical abstract: Image 1 Highlights: The monomer HCQE was electropolymerized on the GPE. After electropolymerization, enrichment with Au nanoparticles was performed to amplify the signal. GOx immobilization was performed on the PHCQE/AuNPs surface using glutaraldehyde as crosslinking reagent. According to stability tests, PHCQE / AuNPs / GOx can be used for long-term studies as a glucose biosensor.